1978
DOI: 10.1002/polc.5070640108
|View full text |Cite
|
Sign up to set email alerts
|

Radical cyclo‐ and cyclocopolymerization

Abstract: Although the principles of cyclopolymerization have been well established, certain aspects of the originally proposed mechanism still remain to be justified in terms of experimental observations. It is the purpose of this paper to discuss these conflicting aspects, to present new information, and to point out those areas where no single mechanistic explanation is presently sufficient. The areas to be considered are: (1) much evidence is available that the cyclization step proceeds via a fast concerted reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…1.4610; 1.1540; IR 1740 (ester C=O), 1640 (vinyl C=C), and 1615 cm-1 (c;: 6.49 (s, 1, trans-CH2 =CCI), and 7.13 ppm (q, 1, =CH-).…”
Section: Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…1.4610; 1.1540; IR 1740 (ester C=O), 1640 (vinyl C=C), and 1615 cm-1 (c;: 6.49 (s, 1, trans-CH2 =CCI), and 7.13 ppm (q, 1, =CH-).…”
Section: Monomersmentioning
confidence: 99%
“…Butler has reconsidered certain aspects of cyclopolymerization mechanism of 1,6-dienes and showed that numerous examples of such polymerizations lead to large fractions of five-membered rings although six-membered rings were predicted on the basis of radical stabilities. 6 Johns et aC as well as Tsukino and Kunitake 8 showed 13 C NMR spectroscopy to be very useful in determining the In a previous paper, we proposed a mechanism for the cyclopolymerization of VA and VMA, 4 in which intermolecular chain propagation was carried out mainly between growing polymer radicals and acrylic or methacrylic groups of monomers, and the intramolecular monocyclization between growing polymer radicals and vinyl groups of a penultimate monomer unit followed the intramolecular bicyclization between monocyclized radicals and the vinyl groups of terminal monomer unit.…”
mentioning
confidence: 99%